The Knights of the Front: Medieval History’s Influence on Great War Propaganda - Haley E Claxton (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2015)
Spanning a number of academic areas, “Knights of the Front: Medieval History’s Influence on Great War Propaganda” focuses on the emergence of medieval imagery in the First World War propaganda. Examining several specific uses of medieval symbolism in propaganda posters from both Central and Allied powers, the article provides insight into the narrative of war, both politically and culturally constructed. The paper begins with an overview of the psychology behind visual persuasion and the history behind Europe’s cultural affinity for “chivalry,” then continues into specific case studies of period propaganda posters that hold not only themes of military glory and prowess, but also themes of race, gender, and religion as well. Finally, the article makes the argument that the realities of the First World War shattered the chivalrous and romantic ideals of war so completely that the concepts and images were no longer appropriate for use as propaganda.
Keywords: Medieval; WWI; propaganda; Joan of Arc; Knights